2010
DOI: 10.1002/polb.22033
|View full text |Cite
|
Sign up to set email alerts
|

Polymers on snow: Toward skiing faster

Abstract: In this study, small-scale model skis running down a Nordic ski track were used to investigate the tribological properties of polymer ski soles of a wide range of chemical compositions and surface structures on snow at temperatures of À2 to À4 C. It was found that ski soles consisting of smooth hydrophilic films of an arithmetical mean surface roughness of less than 0.2 lm experience a considerably higher friction with snow than flat hydrophobic films indicating that for such soles, capillary bridging of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In [6], a laser-structured steel surface had, close to the melting point of ice, a smaller coefficient of friction on ice than a polished one. Analyses on the dependence of different polymer surfaces on snow friction were carried out by Giesbrecht et al [7] and Moldestad [8]. In both studies, the surface roughness had an effect on the measured time during gliding tests.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], a laser-structured steel surface had, close to the melting point of ice, a smaller coefficient of friction on ice than a polished one. Analyses on the dependence of different polymer surfaces on snow friction were carried out by Giesbrecht et al [7] and Moldestad [8]. In both studies, the surface roughness had an effect on the measured time during gliding tests.…”
Section: Introductionmentioning
confidence: 99%
“…[16]. In the case of miniature skis, Giesbrecht and colleagues [17] found that an optimal R a -value for the texture of the ski base was in the range of 0.5-1 µm. When Rohm and co-workers [18] compared two ski bases with completely different textures, they found that they performed similarly at −11.1 ○ C, but one performed better at lower and the other at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For skiing, friction-reducing efforts have focussed on structuring the UHMWPE base material by grinding (Rohm et al, 2015 , 2016 ), imprinting (Breitschädel et al, 2010 ; Nordin and Styring, 2014 ), and sanding (Giesbrecht et al, 2010 ). The development of glide waxes has been industry-driven, and little has reached the scientific literature.…”
Section: Introductionmentioning
confidence: 99%